WTO Reform: A China Round?. (2020) - Gao, Henry
Abstract : Since its accession to the World Trade Organization (WTO), China's exports have been growing exponentially. In 2009, China became the world's top goods exporter. Four years later, China unseated the United States as the top trading nation in the world. In contrast to the burgeoning Chinese economy, the United States and Europe have been suffering from economic decline since the global financial crisis in 2008. China regards its rise as a long overdue restoration of its rightful position, as it has been the largest economy in the world for most of its history, except the brief aberration over the past 150 years. The Western powers, however, view China's rapid development with suspicion, as they attribute China's success mostly to its state-led development model, with state-owned enterprises, massive subsidies, and heavy government intervention playing a major role.